THE RELATIONSHIP BETWEEN KNOWLEDGE, ANXIETY LEVEL, AND FAMILY SUPPORT WITH EXCLUSIVE BREASTFEEDING IN THE COMMUNITY HEALTH CENTER PAUH WORK AREA - Dian Furwasyih; Hardiana, Novi; Novria Hesti; Sunesni; Devi Syarief (PT. Jurnal Center Indonesia Publisher, 2025)
Exclusive breastfeeding in West Sumatra is 74.16%. However, this percentage is still low from the target of the Indonesian Ministry of Health, which is 80%. The purpose of this study is to determine the relationship between family support, knowledge and maternal anxiety levels with exclusive breastfeeding in the Pauh Health Center Working Area in 2024. The type of research is an analytical survey with a cross-sectional approach. The population is all mothers who have babies aged 6-12 months in the Pauh Health Center Working Area with a sample size of 40 respondents. The sample uses total sampling. The research period is February-July. The data collection technique using a questionnaire was analyzed using the Chi Square Test. The results of mothers who provide exclusive breastfeeding were 29 respondents (72.5%), 11 respondents (27.5) did not. The level of knowledge was good 16 respondents (40.0%), sufficient knowledge 12 respondents (30.0%) and less knowledge 12 respondents (30%). Not anxious 21 respondents (52.5%), mild moderate 12 respondents (32.5%) and severe-very severe 6 respondents (15%). Good family support for 22 respondents (55.0%) and poor support for 18 respondents (45%). There is a relationship between maternal knowledge and exclusive breastfeeding, p-value: 0.009 (<α: 0.05), there is no relationship between anxiety and exclusive breastfeeding with p-value: 0.288 there is no relationship between family support and exclusive breastfeeding (>α: 0.05) p-value: 0.377 (p>0.05). The conclusion is that there is a relationship between knowledge and exclusive breastfeeding, the level of anxiety and family support there is no relationship between exclusive breastfeeding. It is hoped that the importance of health workers to provide counseling regarding exclusive breastfeeding to mothers and families at the posyandu in Pisang sub-district, Pauh Health Center Working Area.